Risk-Return Analysis of BSE Sensex Companies - Manjunatha, T. (Indian Journal of Finance, 2009)
Investment in securities market requires the study of the relationship between risks and returns. Researchers in securities market have attempted to understand the relationship between risk and returns and the way securities are priced in the market. These researchers have assumed rational investors and constructed the general equilibrium models of security prices and returns. Sharpe (1964), Lintner (1965) and Mossin (1968) have independently developed the standard form of general equilibrium model for asset returns in securities market. This model has come to be known as Sharpe-Lintner-Mossin form of Capital Asset Pricing Model (CAPM).This model is based on many assumptions about capital market. However, it was served to understand the complex relationship between securities returns and risks. To make this model reflective of the real life situations, researchers have attempted to relax some of the assumptions of standard form of CAPM. Some of the assumptions relaxed by the researchers are absence of personal taxes, unrestricted borrowing and lending at risk-less rate of return, and homogeneous expectations of investors about risks and returns. The studies conducted by Brennan(1971), Black(1972), Fama and Macbeth(1973), Black, Jensen and Scholes (1972), Fama and French(1992,1996) have focused on some of the issues related to CAPM. Research findings of these studies have been debated again and again. The empirical evidence against the CAPM by Fama and French (1992) has generated a lot of debate in the west and has called for major re-examination of the CAPM model. While many studies have been conducted on CAPM in the capital markets of the western countries, there are few studies in the Indian context. Studies by Varma (1988), Yalwar (1988), Srinivasan (1988) have generally supported the CAPM theory. Sudies by Basu (1977), Gupta and Sehgal (1993), Vaidyanathan(1995), Madhusudhan (1997), Sehgal(1997), Ansari(2000), Rao(2004), Manjunatha and Mallikarjunappa (2006,2007)have questioned the validity of CAPM in Indian markets. But Ansari (2000) has opined that the studies of CAPM on the Indian markets are scanty and no robust conclusions exist on this model. In the light of these findings, a sample of Bombay Stock Exchange SENSEX companies listed on the Bombay Stock Exchange have been selected for studying the risk-return relationships. These companies have been selected based on their importance in the early part of the 2000s.